Paon Bali: A Culinary and Local Cultural Education Facility base on Community-Based Tourism - Moch Nur Efendi (Jurnal Sains Terapan Pariwisata, 2026)
The research aim to determine the appeal of Paon Bali in cooking class activities, especially in introducing traditional Balinese food in terms of ingredients, cooking techniques, and moral values.The research uses descriptive qualitative methodology. This study used a qualitative descriptive method, collecting data through in-depth interviews with two experts to explain the layout of Paon Bali and religious matters. To complete the data of 30 respondents from internal students, guests from outside the campus, and guests from abroad (Tiongkok, South Korea and Malaysia) assisted in evaluating the cooking class activities at Paon Bali. Observations were conducted at each activity at Paon Bali, and documentation was obtained from several books and article on Balinese culture. The findings highlight that the cooking class learning at Paon Bali is very helpful in preserving Balinese culture in the field of traditional culinary arts.